On the Size of the Winning Set in the Presence of Interest Groups - Vjollca Sadiraj; Jan Tuinstra; Frans van Winden (Tinbergen Institute, 2005)
Interest groups are introduced in a spatial model of electoral competition between two political parties. We show that the presence of these interest groups increases the winning set, which is the set of policy platforms for the challenger that will defeat the incumbent. Therefore interest groups enhance the probability of the challenger winning the election.
Keywords: D71; D72; 330; Spatial voting models; electoral competition; winning set; interest groups.; Abstimmungsregel; Interessenvertretung; Räumliche Interaktion; Neue politische Ökonomie; Ökonomische Theorie der Demokratie; Wahlkampf